Treating Chronic Stress to Address the Growing Problem of Depression and Anxiety: Biofeedback and Mindfulness as Simple, Effective Preventive Measures. (March 2017) - Steffen, Patrick R.; Austin, Tara; DeBarros, Andrea
Depression and anxiety are undertreated and represent a growing health crisis and economic burden. Current treatment approaches (medications, psychotherapy) appear insufficient to resolve these problems. Difficulties with current treatment approaches include cost, side effects, and stigma. Given that depression and anxiety share significant features and a common etiology in chronic stress, an effective approach to reduce depression and anxiety may be to reduce chronic stress. Chronic stress is on the rise, with more than one third of Americans reporting high levels of stress with which they feel they cannot adequately cope. Treating chronic stress at the population level has the potential to reduce the rising tide of depression and anxiety. Biofeedback and mindfulness are two interventions that demonstrably reduce stress and negative mood, are cost and time-effective, have no side effects, and have minimal stigma relative to medications and psychotherapy.